Siderophores in fluorescent pseudomonads: new tricks from an old dog. (August 2007) - Mossialos, Dimitris; Amoutzias, Grigoris D
Iron is an essential nutrient for almost all bacteria; however, at neutral pH its bioavailability is limited. Siderophores are iron-binding compounds of low molecular weight that enable the microorganisms that produce them to obtain the necessary iron from the environment. Fluorescent pseudomonads include those that are plant growth promoting, human and plant pathogens, as well as bacteria involved in the biodegradation of xenobiotics. Although pyoverdine is the main siderophore produced by different fluorescent pseudomonads, other siderophores produced by fluorescent pseudomonads include pyochelin, (thio)quinolobactin and pyridine-2, 6-bis thiocarboxylic acid. Research on siderophores continues to reveal new information on their regulation, biosynthesis, function and properties. In this review, we focus on recent advances in the field, particularly on newly characterized siderophores produced by fluorescent pseudomonads and their biotechnological potential.